Dynamic Studies on the Response to Humidity of Poly (2‐hydroxyethyl methacrylate) Hydrogels Produced by Initiated Chemical Vapor Deposition. Issue 21 (22nd August 2016) - Unger, Katrin; Resel, Roland; Coclite, Anna Maria
Abstract : The swelling of 2‐hydroxyethyl methacrylate (HEMA) hydrogels, commonly synthesized by solution polymerization, has been widely studied for its practical and fundamental importance. While a good understanding of polymer‐liquid interactions has been established within the Flory‐Huggins framework, little is known about polymer‐water vapor interactions. In this study, the swelling of pHEMA films in response to water and humidity is investigated by means of X‐ray reflectivity and spectroscopic ellipsometry. The hydrogels are synthesized by initiated chemical vapor deposition, using ethylene glycol dimethacrylate (EGDMA) as a crosslinking agent. In water, copolymers of p(HEMA‐ co ‐EGDMA) are stable for an EGDMA fraction above 17%. In a humid atmosphere, even samples with no EGDMA are stable. On increasing the EGDMA fraction, both the swellability in water and in humid environments decreases. The swelling in both environments is related to the mesh size and solubility of the hydrogel, using the Flory‐Huggins theory. The mesh size (average length between two crosslinks) decreases with increasing EGDMA fraction, as expected. The interaction parameter between water vapor and the polymer decreases with increasing relative humidity and reaches 1 ± 0.1 at RH > 75%. Abstract : Humidity‐responsive hydrogels are synthetized by initiated chemical vapor deposition, with defined crosslinking ratios. The swelling in a humid environment is measured in situ by X‐ray reflectivity and related to the mesh size and the solubility of the polymer. It is found that the intermixing between the water vapor and the hydrogels changes with the relative humidity due to molecular rearrangements in the hydrogel's meshes.